Asuhan Keperawatan Post Partum dengan Sectio Caesarea (SC) dengan Masalah Menyusui Tidak Efektif di Ruang Mawar RSUD dr. H. Soewondo Kendal - M. Ulin Nuha; Mudhoifah; Murti Nuryati; Siti Khomsatun (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
This study examines postpartum nursing care for mothers undergoing Sectio Caesarea (SC) with the primary nursing diagnosis of ineffective breastfeeding. The purpose is to evaluate the effectiveness of oxytocin massage intervention in improving breastfeeding outcomes in post-SC mothers. The study was conducted in Mawar Ward, RSUD dr. H. Soewondo Kendal, involving four patients experiencing delayed lactation, difficulty in baby latching, and psychological challenges such as anxiety and lack of confidence. The intervention was based on the Indonesian Nursing Intervention Standards (SIKI), focusing on observation, therapeutic actions, education, and collaboration with healthcare teams and family members. Oxytocin massage was performed 2–3 times daily, complemented by warm compresses, breastfeeding position training, and emotional support. The results indicated significant improvements: increased breast milk production, better baby latching, reduced maternal anxiety, and higher self-confidence in breastfeeding. This evidence-based approach highlights that comprehensive postpartum nursing care—integrating physical, psychological, and family support—plays a crucial role in ensuring breastfeeding success and overall maternal recovery after SC.